Analysis of melting of phase change material inserted a block via impinging turbulent slot jet - Öztop, Hakan Fehmi; Gur, Muhammed; Selimefendigil, Fatih; Cosanay, Hakan (Emerald Group Publishing Ltd, 2023)
PurposeThe purpose of this study is to do a numerical analysis of the jet to a body filled with phase change material (PCM). The melting of the PCM filled body was investigated by the hot jet flow. Four different values of the Reynolds number were taken, ranging from 5 x 103 = Re = 12.5 103. Water, Al2O3 1%, Al2O3 2% and hybrid nanofluid (HNF; Al2O3-Ag mixture) were used as fluid types and the effects of fluid type on melting were investigated. At 60 & DEG;C, the jet stream was impinged on the PCM filled body at different Reynolds numbers. Design/methodology/approachTwo-dimensional analysis of melting of PCM inserted A block via impinging turbulent slot jet is numerically studied. Governing equations for turbulent flow are solved by using the finite element method via analysis and system fluent R2020. FindingsThe obtained results showed that the best melting occurred when the Reynolds number increased and the HNF was used. However, the impacts of using alumina-water nanofluid were slight. At Re = 12,500, phase completion time was reduced by about 13.77% when HNF was used while this was only 3.93% with water + alumina nanofluid as compared to using only water at Re = 5,000. In future studies, HNF concentrations will change the type of nanoenhanced PCMs. In addition, the geometry and jet parameters of the PCM-filled cube can be changed. Originality/valueEffects of impinging jet onto PCM filled block and control of melting via impinging hot jet of PCM. Thus, novelty of the work is to control of melting in a block by impinging hot jet and nanoparticles.
Keywords: Melting; Turbulent flow; PCM; Jet impingement; Heat transfer; CFD